2018
DOI: 10.2169/internalmedicine.0560-17
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Aggressive Mature B-cell Lymphoma Mimicking Immune Thrombocytopenic Purpura

Abstract: A 55-year-old woman suffered from hemorrhagic tendency. She had severe thrombocytopenia without any hematological or coagulatory abnormalities, and a bone marrow examination revealed an increased number of megakaryocytes without any abnormal cells or blasts. No lymphadenopathy or hepatosplenomegaly was observed on computed tomography. She was initially diagnosed with immune thrombocytopenic purpura (ITP). None of the treatments administered for ITP produced a response. However, abnormal cells were eventually f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Therefore, MCL was diagnosed after the first administration of rituximab, so we changed the primary disease target to MCL and administered VR-CAP chemotherapy (bortezomib 1.3 mg/m 2 days 1, 4, 8, and 11; rituximab 375 mg/m 2 day 0; cyclophosphamide 500 mg/m 2 day 1; doxorubicin 33 mg/m 2 day 1; and prednisolone 60 mg/m 2 days 1-5); we modified the dose based on the patient's age. A review of the related literature ( 3 - 15 ) over the past decade confirmed that chemotherapy did not result in severe bleeding in any patients with ITP secondary to NHL. We explained to the patient that previous reports had shown no critical adverse events associated with this chemotherapy but noted that his platelet count was already low (<1.0×10 4 /μL) and might be further reduced as a result of chemotherapy-related bone marrow suppression.…”
Section: Case Reportmentioning
confidence: 89%
“…Therefore, MCL was diagnosed after the first administration of rituximab, so we changed the primary disease target to MCL and administered VR-CAP chemotherapy (bortezomib 1.3 mg/m 2 days 1, 4, 8, and 11; rituximab 375 mg/m 2 day 0; cyclophosphamide 500 mg/m 2 day 1; doxorubicin 33 mg/m 2 day 1; and prednisolone 60 mg/m 2 days 1-5); we modified the dose based on the patient's age. A review of the related literature ( 3 - 15 ) over the past decade confirmed that chemotherapy did not result in severe bleeding in any patients with ITP secondary to NHL. We explained to the patient that previous reports had shown no critical adverse events associated with this chemotherapy but noted that his platelet count was already low (<1.0×10 4 /μL) and might be further reduced as a result of chemotherapy-related bone marrow suppression.…”
Section: Case Reportmentioning
confidence: 89%
“…The international prognostic index (IPI) and hemoglobin platelet (HP) index have been analyzed, but the level of evidence remains to be weak and controversial [ 4 , 5 ]. It is believed that lymphoma tissues produce autoantibodies against platelets that may incite ITP [ 2 ]. Elevated IgG and IgM antiplatelets have been demonstrated in both in vitro and in vivo models supporting this hypothesis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated IgG and IgM antiplatelets have been demonstrated in both in vitro and in vivo models supporting this hypothesis [ 6 ]. Around 10 cases of ITP associated with DLBCL have been reported in literature, highlighting the uniqueness of this presentation [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations